Comparative Analysis of Corrosion Monitoring Results between Resistance Probe Technology and Weight Loss Method - WANG Yi-pin, AN Jiang-feng (Cailiao Baohu)
Owing to the conventional corrosion coupon method hardly meeting the data amount requirement of corrosion industry, the correlation of corrosion rate between the resistance probe monitoring technology and the traditional weightlessness method in Wuhan’s atmospheric environment was studied.Results showed that in an atmospheric environment with 5 ℃≤θ≤ 35 ℃ and relative humidity RH≥60%.The corrosion rate obtained by the corrosion coupon method was 1.3 times that obtained by the resistance probe technology.Within the above temperature and humidity range, the higher the temperature and humidity, the higher the corrosion rate, and the interaction between the two had a positive effect on the corrosion rate.Compared with the corrosion coupon method, the resistance probe technology had a better real-time monitoring effect.